Experimental bladder carcinogenesis – rodent models - Oliveira, P.A.; Colaco, A.; L.F. De la Cruz, P.; Lopes, C. (Experimental Oncology, 2006)
Several rodent models of bladder cancer development have been established. The aim of this review article is to provide a critical
assessment of different animal models available for the study of bladder carcinogenesis, its chemoprevention and therapy. All, except
for transgenic and knockout animals, require 8–12 months experimental periods in order to generate a high yield of neoplasias.
Spontaneous bladder tumor models are extremely rare. The significance of the results from animal experiments is dependent upon the
selection of a suitable animal model. There are no rules regarding the choice of a model, it is however very useful to have knowledge
of relevant comparative medical aspects concerning this subject. We describe chemical carcinogens most commonly used to induce
bladder cancer, pellet implantation and urinary calculi, agents that promote bladder cancer, and irradiation. We also evaluated
other tools such as cell cultures, tumor implantation and transgenic models for bladder cancer, that have been developed to study
the process. The review considers how several imaging techniques can be applied to study rodent bladder carcinogenesis. Для изучения механизмов развития рака мочевого пузыря было создано несколько экспериментальных моделей на гры-
зунах. Целью обзора была сравнительная оценка различных экспериментальных моделей для изучения канцерогенеза
мочевого пузыря, профилактики и терапии. За исключением трансгенных и нокаутных животных, для получения высокого
выхода опухолей в любой экспериментальной модели требуется 8–12 мес. Модели спонтанного канцерогенеза мочевого
пузыря крайне редки. Выбор экспериментальной модели с определенными параметрами определяет значимость получен-
ных результатов. В статье описаны различные методики, используемые для индукции рака мочевого пузыря in vivo, ряд
методических подходов, таких как культура клеток, имплантация опухоли и трансгенные модели рака мочевого пузыря
и современные методы мониторинга опухолевой прогрессии.